Characterization of resistant MCF-7 breast cancer cells developed by repeated cycles of photodynamic therapy - Aniogo, Eric Chekwube; George, Blassan P.; Abrahamse, Heidi (Frontiers in Pharmacology, 2022)
Breast cancer mainly affects women and causes a severe global threat to health. It is often managed and treated with surgery, chemotherapy, immunotherapy, and radiation therapy. Generally, chemotherapy as a treatment option is often opposed by responsive tumor relapse and development of resistance, a significant setback of current treatment. Photodynamic therapy (PDT) offers a promising modality that can treat cancer by combining a photosensitizer and laser irradiation in the presence of oxygen. However, one problem of PDT in treating breast cancer is the apparition of the resistant cell population. Thus, we aimed for stepwise selection and characterization of MCF-7 cells resistant to PDT with sulfonated zinc phthalocyanine (ZnPcS4) photosensitizer. The wild-type MCF-7 was exposed to successive cycles of ZnPcS4-PDT, and ten resistant populations were finally obtained. In wild-type and parental cells, we analyzed the cell morphology (light microscopy), cell cycle (BrdU staining), cell viability (MTT assay), antioxidant activity (superoxide dismutase measurement), and immunofluorescence expression of resistant p-glycoprotein (P-gp). The results obtained indicate that resistant cells showed a mesenchymal cell phenotype, few differences in antioxidant activity, an increased DNA synthesis, and more expression of P-gp than the wild-type parental cells. These distinctive features of resistant cells can provide insight into the emergence of MCF-7 cell resistance to PDT, which was necessary to design the best therapeutic procedure for improved efficacy.